Maimonides’ intellectual portrait a critique of simplistic approaches - Visi, Tamás (Acta Scientiarum Socialium, 2011)
The characteristics of Maimonides’ thought, works, and career can be understood in the context of the new social and intellectual challenges that medieval Jewish communities in the Mediterranean basin had to face during the twelfth century. The disintegration of traditional Jewish culture in Andalusia, a new type of Islamic polemic against Judaism, and the decrease of rabbinic authority all contributed to Maimonides’ conviction that Judaism was experiencing a profound crisis in his time. Much of Maimonides’ oeuvre can be seen as a series of attempts to overcome this crisis. Adopting the Aristotelian concept of mental language, Maimonides attempted to establish a new culture of reading traditional Jewish texts. Adopting philosophical theories of good life, he proposed a new ideal for the future Jewish religious leadership.